A Near-consensus: Israel's Security Establishment and the Two-state Solution. Issue 3 (4th May 2019) - Shaver, Benjamin L.; Ziv, Guy
Abstract : A clear majority of Israel's retired high-ranking military and intelligence officials support the establishment of a separate Palestinian state.